Muslim Youths and Societal Development: The Case of Nasarawa State - Sule, Muhammad Maga (IAIN Surakarta, 2018)
A linkage between Muslim youths and societal development is obvious and enduring since the time of the first Prophet on earth, Adam (A.S.). This interaction is connected symbiotically and, furthermore, one depends on the other for its sustenance. Therefore, the role of Muslim youths in the development of Nasarawa State cannot be ignored. The wheels of the development of a country rest on the shoulders of the youths. Consequently, the youths in Nasarawa State are the engine of the growth and development because they provide the labor force for the production of goods and services to take effect in the development of the state. Thus, the role of Muslim youths in the development of Nasarawa State is crucial for the entire developmental processes and aspirations of the whole society. Â In addition, the productive youths are acknowledged as the cornerstone for societal rejuvenation.Â Keywords:Youth, Social Development, Nasawara State